IEEE Information Theory Workshop, 2005. 2005
DOI: 10.1109/itw.2005.1531888
|View full text |Cite
|
Sign up to set email alerts
|

Bounds on the entropy of patterns of I.I.D. sequences

Abstract: Abstract-Bounds on the entropy of patterns of sequences generated by independently identically distributed (i.i.d.) sources are derived. A pattern is a sequence of indices that contains all consecutive integer indices in increasing order of first occurrence. If the alphabet of a source that generated a sequence is unknown, the inevitable cost of coding the unknown alphabet symbols can be exploited to create the pattern of the sequence. This pattern can in turn be compressed by itself. The bounds derived here a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 15 publications
3
27
0
Order By: Relevance
“…Furthermore, better universal compression performance is also possible in the case where the alphabet size k is sublinear in n or even fixed. Moreover, even better non-universal compression is sometimes possible because every pattern represents a collection of many sequences, thus reducing the overall pattern entropy (see, e.g., [31], [34], [36], [38], [39]). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, better universal compression performance is also possible in the case where the alphabet size k is sublinear in n or even fixed. Moreover, even better non-universal compression is sometimes possible because every pattern represents a collection of many sequences, thus reducing the overall pattern entropy (see, e.g., [31], [34], [36], [38], [39]). …”
Section: Introductionmentioning
confidence: 99%
“…Since # % ¥ S R ¡ is the result of data processing, its entropy must be no greater than . Subsequently to the results in [14], it was independently shown in [4] and [8] that for discrete i.i.d. sources, the pattern entropy rate is equal to that of the underlying i.i.d.…”
mentioning
confidence: 86%
“…The first results on pattern entropy in [11], [14], [16], however, showed that for sufficiently large alphabets, the pattern block entropy must decrease from the i.i.d. one even more significantly than the universal coding penalty for coding patterns.…”
mentioning
confidence: 99%
“…It was first introduced byÅberg in [8] as a solution to the multi-alphabet coding problem, where the message x contains only a small subset of the known alphabet A. It was further studied and motivated in a series of articles by Shamir [9][10][11][12] and by Jevtić, Orlitsky, Santhanam and Zhang [13][14][15][16] for practical applications: the alphabet is unknown and has to be transmitted separately anyway (for instance, transmission of a text in an unknown language), or the alphabet is very large in comparison to the message (consider the case of images with k = 2 24 colors, or texts when taking words as the alphabet units).…”
Section: Dictionary and Patternmentioning
confidence: 99%
“…To explain the notion of pattern, let us take the example of [9]: string x = "abracadabra" is made of n = 11 characters. The information it conveys can be separated in two blocks:…”
Section: Dictionary and Patternmentioning
confidence: 99%